Situational strategic versus personal influences on negotiation medium choice: Media synchronicity theory and affect for communication channel. Issue 3 (11th June 2018) - Geiger, Ingmar; Laubert, Christoph
Abstract : Purpose: This study aims to compare predictions from media synchronicity theory (MST) with the influence of personality variables in an attempt to explain how negotiators choose the communication media for negotiation. Design/methodology/approach: The authors examine media choice in two scenario-based experimental studies with students ( n = 209) and professionals ( n = 302) in a negotiation setting. For the analysis of the data, the authors use multilevel modeling. Findings: This study offers support for the central proposition of MST, namely, that the type of communication subtask (conveyance or convergence) determines the degree of media synchronicity needed and therefore media choice (face-to-face or email). The support for its boundary conditions and contingent situational determinants is weaker. With the affect for communication channel scale, this study also captures individual media preferences for face-to-face or email communication, which have consistent influences on negotiators' media choice. The personal influence variables on average account for similar variance in the data compared with the MST-based determinants. Originality/value: This study sheds new light on diverging empirical results concerning media influences in negotiation and offers some reconciling suggestions. Furthermore, this study is the first to test boundary conditions of MST. Also, it stresses the importance of negotiators' media preferences for media choice.